2017
DOI: 10.2217/rme-2017-0073
|View full text |Cite
|
Sign up to set email alerts
|

Preservation and Stability of Cell Therapy Products: Recommendations from an Expert Workshop

Abstract: If the field of regenerative medicine is to deliver therapies, rapid expansion and delivery over considerable distances to large numbers of patients is needed. This will demand efficient stabilization and shipment of cell products. However, cryopreservation science is poorly understood by life-scientists in general and in recent decades only limited progress has been made in the technology of preservation and storage of cells. Rapid translation of new developments to a broader range of cell types will be vital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 57 publications
0
23
0
1
Order By: Relevance
“…More recently RFID tags compatible with LN 2 storage temperatures and capable of being retro-fitted to standard cryovials have been introduced (Cryogatt, www.cryogatt.com). Ultra-cold-resistant chips are being developed which, when fitted within individual cryovials, could store not only a detailed thermal history but also detailed batch information, test results, and other relevant quality documentation [14]. …”
Section: Choice Of Container Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently RFID tags compatible with LN 2 storage temperatures and capable of being retro-fitted to standard cryovials have been introduced (Cryogatt, www.cryogatt.com). Ultra-cold-resistant chips are being developed which, when fitted within individual cryovials, could store not only a detailed thermal history but also detailed batch information, test results, and other relevant quality documentation [14]. …”
Section: Choice Of Container Systemmentioning
confidence: 99%
“…However, a recent prospective, multicentre surveillance study has suggested that factors unrelated to the CPA may be the cause of these reactions [45]. The debate surrounding the use of DMSO has led to a call for a proper assessment of the issues surrounding its use [14]. …”
Section: Choice Of Cpamentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels are the most common materials used as the substrate for CMs. Hydrogels of gelatin‐methacrylate, hyaluronan, alginate, and gelatin have hydrophilic surfaces or specific moieties that have affinity to the receptors on the cell membranes . Hydrogels may be cast into a specific pattern, like paralleled channels, to allow for improved myofiber alignment and sarcomere maturity of CMs along the patterns .…”
Section: Application Of Biomaterials Engineering In CM Differentiatiomentioning
confidence: 99%
“…This strategy does not require cell dissociation and can gently remove undifferentiated PSCs to eliminate teratoma formation after transplantation in vivo. Undifferentiated PSCs are known to cause teratoma due to uncontrolled spontaneous differentiation . Antibiotic resistance genes can be used for purification of hPSC‐derived CMs with genetic modification.…”
Section: Remaining Challenges Of Using Pscs For MI Therapymentioning
confidence: 99%